2002
DOI: 10.1007/s00775-002-0340-8
|View full text |Cite
|
Sign up to set email alerts
|

A paramagnetic probe to localize residues next to carboxylates on protein surfaces

Abstract: It is shown that the paramagnetic properties of lanthanides can be exploited to obtain information on specific parts of a protein surface. Owing to the high affinity of coordinatively unsaturated lanthanide complexes for oxygen donors, carboxylate groups can be used as preferential targets for the interaction. The DO3A ligand is particularly useful in these studies, as it coordinates lanthanides in a heptadentate fashion, leaving two sites available for exogenous donors. A solution of a (15)N-labeled sample pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 40 publications
5
31
0
Order By: Relevance
“…Other paramagnetic metal chelate complexes, such as Mn 2þ -NTA and Gd 3þ -EDTA, did not bind specifically to the histidine residues for three proteins possessing a poly hisitidine tag; HR23B UbL, IRF4 DBD and the S5a UbL binding region [18]. These results are consistent with hard-soft-acid-base (HSAB) theory [25][26][27].…”
Section: Discussionsupporting
confidence: 78%
“…Other paramagnetic metal chelate complexes, such as Mn 2þ -NTA and Gd 3þ -EDTA, did not bind specifically to the histidine residues for three proteins possessing a poly hisitidine tag; HR23B UbL, IRF4 DBD and the S5a UbL binding region [18]. These results are consistent with hard-soft-acid-base (HSAB) theory [25][26][27].…”
Section: Discussionsupporting
confidence: 78%
“…Paramagnetic effects can be used in protein NMR analysis by addition of transition metals, [1,2] lanthanide ions, [3,4] lanthanide chelates, [5][6][7][8][9][10] stable radicals, such as 2,2,6,6-tetra-A C H T U N G T R E N N U N G methylpiperidine-1-oxyl (TEMPO), [11][12][13][14][15][16] or dioxygen, [17] to decrease the signal overlap of the resonances observed, to probe the molecular surface of these large molecules, or to align macromolecules for residual dipolar-coupling measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that the hydration number can be different for a complex bound to a protein target than for the complex in aqueous solution. [11,12] To design high-relaxivity contrast agents, it is important to be able to account for the various parameters affecting nuclear relaxation. The magnetic-field dependence of relaxivity gives only indirect insight into the metal coordination sphere, since a variety of parameters can be responsible for relaxivity and the change in relaxivity upon protein binding.…”
Section: Introductionmentioning
confidence: 99%